2021
DOI: 10.3390/toxins13080575
|View full text |Cite
|
Sign up to set email alerts
|

A Spider Toxin Exemplifies the Promises and Pitfalls of Cell-Free Protein Production for Venom Biodiscovery

Abstract: Arthropod venoms offer a promising resource for the discovery of novel bioactive peptides and proteins, but the limited size of most species translates into minuscule venom yields. Bioactivity studies based on traditional fractionation are therefore challenging, so alternative strategies are needed. Cell-free synthesis based on synthetic gene fragments is one of the most promising emerging technologies, theoretically allowing the rapid, laboratory-scale production of specific venom components, but this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…The snake venom kallikrein was later expressed in the same system, and the bioactivity was similar to its natural counterpart in vitro ( Wang et al, 2012 ). Other cell-free production systems have recently been compared for their ability to produce an ICK toxin from the sicariid spider Hexophthalma dolichocephala ( Lüddecke et al, 2021 ). This showed that only one system (based on E. coli ) was able to produce a bioactive toxin in low amounts and unclear folding, whereas the other systems failed to yield any product at all ( Lüddecke et al, 2021 ).…”
Section: How Synthetic Biology Enables Access To Venom Gene Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…The snake venom kallikrein was later expressed in the same system, and the bioactivity was similar to its natural counterpart in vitro ( Wang et al, 2012 ). Other cell-free production systems have recently been compared for their ability to produce an ICK toxin from the sicariid spider Hexophthalma dolichocephala ( Lüddecke et al, 2021 ). This showed that only one system (based on E. coli ) was able to produce a bioactive toxin in low amounts and unclear folding, whereas the other systems failed to yield any product at all ( Lüddecke et al, 2021 ).…”
Section: How Synthetic Biology Enables Access To Venom Gene Productsmentioning
confidence: 99%
“…Other cell-free production systems have recently been compared for their ability to produce an ICK toxin from the sicariid spider Hexophthalma dolichocephala ( Lüddecke et al, 2021 ). This showed that only one system (based on E. coli ) was able to produce a bioactive toxin in low amounts and unclear folding, whereas the other systems failed to yield any product at all ( Lüddecke et al, 2021 ). The authors therefore recommended the optimization of cell-free systems and protocols to maximize protein yield and folding specificity ( Lüddecke et al, 2021 ).…”
Section: How Synthetic Biology Enables Access To Venom Gene Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hierfür steht mittlerweile eine ganze Bandbreite an Methoden zur Verfügung, wobei die hetero loge Expression in Bakterienzellen noch immer am häufigs ten eingesetzt wird. In jüngerer Vergangenheit wurden aber auch Technologien in eukaryotischen Zellen und so gar vollkomen zellfreie Ansätze verwendet um Bestandteile aus Tiergiften im Labor herzustellen [17][18][19].…”
Section: Das Junge Forschungsfeld "Venomics"unclassified
“…More recent venomics strategies combine proteomics and transcriptomics to shed light on the composition of venoms [21]. When combined with biotechnology, this approach provides access to all venom proteins and peptides in a given source [22]. A major insight from modern venomics is that spider venoms not only contain small ICK peptides but also an array of high-molecular-weight proteins, often with putative enzymatic activity [2,23].…”
Section: Introductionmentioning
confidence: 99%